Design and implementation of a wireless device variable monitor with data acquisition through telegram (Ingenio Magno, 2018)
The article introduces the design, development and implementation of a wireless transmission system for monitoring the behavior of five physical variables through Telegram. The strategy of data acquisition regardless of the location in which the user who monitors these variables is located and which can be viewed by any mobile device, is based on the Telegram API that provides the possibility to consult during the 24 hours of the day the behavior of the wireless device variables in the area or place being evaluated. Each of the sensors used is described, the signal conditioning stage for the connection with the ATSAMD21G18 microcontroller, which has the function of capturing and digitizing the analog signals of the sensors in order to carry out the transmission stage. In addition, we will deepen the operation of the Telegram API and the respective connections for data acquisition. The variables to be measured are temperature, humidity, compass, inclination lux.
Keywords: brújula; estación climática; humedad; internet de las cosas; lux; telegram; temperatura